Achieving Drug and Alcohol Abstinence Among Recently Incarcerated Homeless Women: A Randomized Controlled Trial Comparing Dialectical Behavioral Therapy-Case Management With a Health Promotion Program. Issue 6 (November 2017) - Nyamathi, Adeline M.; Shin, Sanghyuk S.; Smeltzer, Jolene; Salem, Benissa E.; Yadav, Kartik; Ekstrand, Maria L.; Turner, Susan F.; Faucette, Mark
Abstract : Background: Homeless female ex-offenders (homeless female offenders) exiting jail and prison are at a critical juncture during reentry and transitioning into the community setting. Objective: The purpose of the study was to compare the effect of a dialectical behavioral therapy-case management (DBT-CM) program with a health promotion (HP) program on achieving drug and alcohol abstinence among female parolees/probationers residing in the community. Methods: We conducted a multicenter parallel randomized controlled trial with 130 female parolees/probationers (aged 19–64 years) residing in the community randomly assigned to either DBT-CM ( n = 65) or HP ( n = 65). The trial was conducted in four community-based partner sites in Los Angeles and Pomona, California, from February 2015 to November 2016. Treatment assignment was carried out using a computer-based urn randomization program. The primary outcome was drug and alcohol use abstinence at 6-month follow up. Results: Analysis was based on data from 116 participants with complete outcome data. Multivariable logistic regression revealed that the DBT-CM program remained an independent positive predictor of decrease in drug use among the DBT-CM participants at 6 months ( p = .01) as compared with the HP program participants. Being non-White ( p < .05) and having higher depressive symptom scores ( p < .05) were associated with lower odds of drug use abstinence (i.e., increased the odds of drug use) at 6 months. Discussion: DBT-CM increased drug and alcohol abstinence at 6-month follow-up, compared to an HP program.